Heavy Metals Biosorption Phenomena Of Cr, Fe, Zn, Cu, Ni, And Mn on the Biomass of Mixed Bacteria of Bacillus, Pseudomonas, Arthrobacter and Aeromonas - Zainus Salimin; Endang Nuraeni (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
The bacterial biomass having the capability of ions biosorption is utilized for the treatment of industrial waste water containing ions pollutant. The Extracellular Polymeric Substance (EPS) on the bacteria functions to support that biosorption mechanism. The EPS has the composition of polysaccharides (40-95% of total EPS), protein (1-60%), nucleic acids (1-10%), lipids (1-10%), and polymer of amino acid and other compounds of bacterial origin. The result of experiment indicates that the pH of 7 and process period of 560 hours was the best of process condition giving the decreasing of BOD and COD on the value of 38 and 74 ppm. On the pH of 6 and 8 the value of BOD and COD are 52 and 102 and 47 and 92 respectively